Ethnography, the Internet, and Youth Culture: Strategies for Examining Social Resistance and “Online‐Offline” Relationships - Wilson, Brian (Canadian Journal of Education/Revue canadienne de l’éducation, 2006)
The integration of traditional (offline and face‐to‐face) and virtual ethnographic methods can aid researchers interested in developing understandings of relationships between online and offline cultural life, and examining the diffuse and sometimes global character of youth resistance. In constructing this argument, I have used insights from studies on youth activism and the rave subculture. These studies also informed my central theoretical suggestion: that an approach to research underscored by a sensitivity to everyday experiences and the power structures framing these experiences can (still) be a powerful guide for understanding flows and circuits of resistance in Internet‐influenced cultures. Key words: globalization, qualitative research, social movements, rave culture, virtual ethnography L’intégration de méthodes ethnographiques traditionnelles (hors ligne et en présentiel) ou recourant aux TIC peut aider les chercheurs à mieux comprendre les relations entre la vie culturelle en ligne et hors ligne et à étudier le caractère diffus et parfois planétaire de la résistance des jeunes. L’auteur fonde son argumentation sur des observations tirées d’études portant sur l’activisme chez les jeunes et la sous‐ culture techno‐rave. Ces études servent également de point de départ à l’hypothèse centrale de l’auteur, à savoir qu’une approche de la recherche qui est sensible aux expériences quotidiennes et aux structures du pouvoir encadrant ces expériences peuvent (encore) servir de guide précieux pour comprendre les courants et circuits de résistance dans les cultures sous l’influence d’Internet. Mots clés : mondialisation, recherche qualitative, mouvements sociaux, culture techno‐rave, ethnographie virtuelle